2022
DOI: 10.3390/ijms232415744
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli Expressed Multi-Disulfide Bonded SARS-CoV-2 RBD Shows Native-like Biophysical Properties and Elicits Neutralizing Antisera in a Mouse Model

Abstract: A large-scale Escherichia coli (E. coli) production of the receptor-binding domain (RBD) of the SARS-CoV-2 could yield a versatile and low-cost antigen for a subunit vaccine. Appropriately folded antigens can potentially elicit the production of neutralizing antisera providing immune protection against the virus. However, E. coli expression using a standard protocol produces RBDs with aberrant disulfide bonds among the RBD’s eight cysteines resulting in the expression of insoluble and non-native RBDs. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…The need to obtain a glycosylated form of RBD is currently debatable. On the one hand, a fairly large number of studies have been published on the E. coli expressed RBD, which not only made it possible to obtain effective antibodies against the SARS-CoV-2 virus but also demonstrated its direct interaction with ACE2 with an efficiency close to the deglycosylated product (see, for example, [ 31 , 52 , 53 ]). It has also been shown that de-glycosylation of recombinant RBD samples expressed in mammalian cells does not significantly reduce the effectiveness of their interaction with ACE2 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need to obtain a glycosylated form of RBD is currently debatable. On the one hand, a fairly large number of studies have been published on the E. coli expressed RBD, which not only made it possible to obtain effective antibodies against the SARS-CoV-2 virus but also demonstrated its direct interaction with ACE2 with an efficiency close to the deglycosylated product (see, for example, [ 31 , 52 , 53 ]). It has also been shown that de-glycosylation of recombinant RBD samples expressed in mammalian cells does not significantly reduce the effectiveness of their interaction with ACE2 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized gene was inserted into pET15b at the NdeI/BamH1 with ampicillin resistance ( Supplementary Figure S1a ). The RBD was expressed in E. coli T7 SHuffle cells and purified from inclusion bodies as explained elsewhere [ 18 ]. The RBD proteins tagged by 6-Histidines were purified using denaturing open nickel-nitrilotriacetic acid (Ni-NTA) (Wako, Japan) chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were carried out under the condition of 10 mM Hepes buffer (pH 6.5) at a protein concentration of 0.3 mg/mL. The spectroscopic measurements: Far-UV circular dichroism (CD), Tryptophan fluorescence, Dynamic light scattering (DLS), and Static light scattering (SLS) were carried out, in essence, as reported previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, spike contains many immunogenic hotspots. As a result, it is the prime target for vaccine and neutralizing antibody development [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%